Proland (Real Estate Management Portal) - Bhoyar, A; Ramteke, S; Kumbhare, A (International Journal of Computer Sciences and Engineering, 2025)
This website is designed to attend to all your needs- from buying property, selling property or renting /leasing property. Here you found better opportunity to invest your value of entire life. PROLAND application is an internet portal dedicated to meet every aspect of the user needs in the real Estate industry. It is application where property owners, brokers and investors can exchange information, selling and buying property, quickly effectively and inexpensively. It features commercial and residential properties for sells and rents. The PROLANDS application show the names of all property owners, how long a particular holder owned it, and the price of the land when it was sold. Rarely will a PROLAND application mention capital improvements to the property. PROLAND is a web application. It can be accessed by any where in the world.it overcome the mediators, it direct communication between owner and purchaser